2019
DOI: 10.3233/jvr-191027
|View full text |Cite
|
Sign up to set email alerts
|

Differences in youth and parent postsecondary expectations for youth with disabilities

Abstract: BACKGROUND: Parent expectations are known to be significant predictors of postsecondary outcomes among youth with disabilities. However, little is known about the relationship between parent and youth expectations and their differential prediction of postsecondary outcomes among youth with disabilities. OBJECTIVE:To determine the relationship between parent and youth expectations among students with disabilities in the United States. METHODS:Through analysis of the National Longitudinal Transition Study-2 (NLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A quantitative study also looked at the parentadolescent agreement related to transition; a longitudinal analysis of 1940 students with a wide range of disabilities (including autism) suggested that the postsecondary expectations of parents and adolescents weakly-to-moderately correlated with each other. 24 Adolescents' expectations were consistently more independent (e.g., living in the community and earning enough to support themselves) than the expectations of their parents. 24 The authors also found that both adolescents' and parents' expectations predicted youth postsecondary outcomes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A quantitative study also looked at the parentadolescent agreement related to transition; a longitudinal analysis of 1940 students with a wide range of disabilities (including autism) suggested that the postsecondary expectations of parents and adolescents weakly-to-moderately correlated with each other. 24 Adolescents' expectations were consistently more independent (e.g., living in the community and earning enough to support themselves) than the expectations of their parents. 24 The authors also found that both adolescents' and parents' expectations predicted youth postsecondary outcomes.…”
Section: Introductionmentioning
confidence: 98%
“…24 Adolescents' expectations were consistently more independent (e.g., living in the community and earning enough to support themselves) than the expectations of their parents. 24 The authors also found that both adolescents' and parents' expectations predicted youth postsecondary outcomes. Specifically, adolescents' expectations were stronger predictors of their postsecondary outcomes in the areas of education and independent living, whereas parents' expectations were stronger predictors of employment and financial independence.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Given that a goal of secondary education is to develop students with disabilities who are self-determined, youth should have expectations and the said expectations should impact their educational and post-school planning and goals. Within the literature, examining the expectations of youth with disabilities, Kirby et al (2019) concluded that students’ expectations for themselves were higher than their parents. Using data from the NLTS2, Kirby et al (2019) found youth expectations predicted independent living and post secondary education to a greater extent, whereas parent expectations were more associated with employment.…”
mentioning
confidence: 99%
“…Within the literature, examining the expectations of youth with disabilities, Kirby et al (2019) concluded that students’ expectations for themselves were higher than their parents. Using data from the NLTS2, Kirby et al (2019) found youth expectations predicted independent living and post secondary education to a greater extent, whereas parent expectations were more associated with employment. Previous researchers also reported higher youth expectations than parental expectations (Wagner et al, 2007).…”
mentioning
confidence: 99%